Spatial population dynamics of a specialist aphid parasitoid, Lysiphlebus hirticornis Mackauer (Hymenoptera: Braconidae: Aphidiinae): evidence for philopatry and restricted dispersal - Nyabuga, Franklin N.; Loxdale, H. D.; Heckel, D.; Weisser, W. (My University, 2010)
Within insect communities, the population ecology of organisms representing higher trophic levels, for example, hymenopterous parasitoids, may be influenced by the structure of their insect hosts. Using microsatellite markers and ecological data, we investigated the population structure of the specialist braconid wasp parasitoid, Lysiphlebus hirticornis Mackauer attacking Metopeurum fuscoviride, a specialist aphid feeding on tansy, Tanacetum vulgare. Previous studies revealed that M. fuscoviride has a classic metapopulation structure with high subpopulation turnover. In this study, up to 100% of ramets within a host plant genet colonized by aphids were colonized by the parasitoid, yet plants with aphids but no parasitoids were also observed. Genetic differentiation measured by FST, actual differentiation (D) and relative differentiation (GST) indicated highly structured parasitoid population demes, with restricted gene flow among and between parasitoid subpopulations at the various sites. Interestingly, both field data and population assignment analysis showed that the parasitoid is highly philopatric. Thus, despite the frequent local extinctions of the aphid host, the parasitoid continuously exploits its aphid host and contributes to the demise of local aphid subpopulations, rather than spreading its genes over many aphid populations. FST values for the haplodiploid parasitoid were similar to those found in an independent study of the diploid aphid host, M. fuscoviride, hence supporting the view that an insect herbivore’s population structure directly influences the ecology and genetics of the higher trophic level, in this case the wasp parasitoid.
Keywords: L. hirticornis; M. fuscoviride; microsatellites; philopatry; isolation by distance; gene flow